Weedy plants of Ayer Hitam Forest Reserve, Selangor - Mansor, Asyraf; Mansor, Mashhor (Universiti Putra Malaysia Press, 2001)
The Ayer Hitam Forest Reserve has possibly been under constant threat from invasive species especially the weeds from surrounding development sites. The total number of weed taxa identified from this forest were 33 species, 29 genera and J3 families. Of these taxa, only two species aquatic weeds vizs., Ceratopteris thalictroides (Parkeriaceae) and Hydrilla venieillata (Hydrocharitaceae). The most dominant terrestrial weedy speeies in this forest were Clidemia hirta (Melastomataceae) and Chromalaena odorata (Compositae). All grasses and sedges !lIJi~si,~s were recorded at the disturbed sampling sites only. Limosa pigra was only found at the most disturbed site bordering the forest.